A 10-day mild treadmill exercise performed before an epileptic seizure alleviates oxidative injury in the skeletal muscle and brain tissues of the rats - KAYA, ÖZLEM TUĞÇE; YEGEN, BERRAK; YÜKSEL, MERAL; YILDIRIM, ALPER (My University, 2022)
© 2022 Marmara University Press, All Rights Reserved.Objective: Epileptic seizures may cause skeletal muscle injury and memory dysfunctions. The present study was aimed to investigate the possible protective effects of exercising prior to seizure on seizure-induced oxidative injury in the skeletal muscle and brain. Materials and Methods: Sprague-Dawley male rats were assigned as non-exercise (n=16) and exercise groups (n=16). Following a 3-day exercise training, exercise protocol (30 min) was performed on a treadmill for 10 days, while control rats had no exercise. On the 11th day, the epileptic seizure was induced by a single intraperitoneal injection of pentylenetetrazol (PTZ) (45 mg/kg), while the control groups were injected with saline. Passive-avoidance test was initially performed before PTZ/saline injection and repeated 72 h later for the assessment of memory function. Brain and gastrocnemius muscles were taken for histological assessments and to determine the levels of malondialdehyde (MDA) and glutathione (GSH), myeloperoxidase (MPO) activity and luminal – and lucigenin – enhanced chemiluminescence levels. Results: Exercise training alone increased the formation of reactive oxygen species and elevated the antioxidant GSH capacity of the muscle tissue in the control rats, but these effects were not observed in the muscles of the exercised rats induced with a PTZ-seizure. On the other hand, short-term exercise alone had no effect on the basal oxidative parameters of the brain tissues. Prior exercise did not alter the average seizure scores or memory performances when compared to non-exercised groups, but suppressed the PTZ-induced elevations in MDA and chemiluminescence levels as well as MPO activity in the brain. Conclusion: A 10-day mild treadmill exercise reduced the oxidative brain damage due to a single seizure-induced excitotoxicity and exerted a preconditioning effect on the skeletal muscles exposed to tonic-clonic contractions.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Epileptic seizure; Exercise; Oxidative damage; Memory dysfunction; Skeletal muscle; PILOCARPINE-INDUCED SEIZURES; PHYSICAL-EXERCISE; COGNITIVE IMPAIRMENT; NITRIC-OXIDE; STRESS; DAMAGE; ANTIOXIDANTS; INFLAMMATION; MEMORY; LIGHT; Epileptic seizure; Exercise; Oxidative damage; Memory dysfunction; Skeletal muscle